FAKTOR YANG MEMENGARUHI PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA WANITA USIA SUBUR - Putu Wahyuni Wulandari Karnawati; Ni Luh Putu Suariyani (ARCHIVE OF COMMUNITY HEALTH, 2022)
Globally and in Indonesia, the discovery of breast cancer cases in 2020 has increased compared to 2018. The increase in cases is not comparable to early detection efforts, one of which is BSE. The purpose of this study is to describe BSE behavior in reproductive age women in Mataram and the factors that influence through the Precede Proceed theory. The independent variables were age, education, knowledge, attitudes, information exposure and social support, while the dependent variable was BSE behavior. The type of research is analytic observational with a cross sectional study design. The inclusion criteria are women aged 20-49 years live in Mataram City with a sample size of 170 WUS. The sampling technique were voluntary and snowballing sampling. Data were analyzed by descriptive analysis, different proportion test and logistic regression. The results showed that four variables had a significant influence on BSE behavior, namely age category (OR=4.47:95%CI=1.18–16.96), knowledge (OR=57.42:95%CI=6.16– 534.64), family support (OR=13.14:95%CI=0.50–341.32) and friend support (OR=6.64:95%CI=0.98–44.59). The results of this study are expected to encourage the community to be able to provide mutual support, as well as an increase in educational programs related to BSE. Keywords: BSE, Reproductive Age Women, Precede Proceed Theory